2017
DOI: 10.1103/physrevphyseducres.13.020115
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of interactive tutorials in promoting “which-path” information reasoning in advanced quantum mechanics

Abstract: Research suggests that introductory physics students often have difficulty using a concept in contexts different from the ones in which they learned it without explicit guidance to help them make the connection between the different contexts. We have been investigating advanced students' learning of quantum mechanics concepts and have developed interactive tutorials which strive to help students learn these concepts. Two such tutorials, focused on the Mach-Zehnder interferometer (MZI) and the double-slit exper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

6
4

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 50 publications
0
13
0
1
Order By: Relevance
“…Furthermore, we found that students who were enrolled in QM courses that used active learning methods, such as peer instruction and tutorials, performed better on the QMFPS than those who did not. These approaches included active learning techniques such as peer instruction [52,53], tutorials [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68], cooperative group problem solving [69], and Just-In-Time-Teaching [70,71], to help students develop a coherent knowledge structure of the formalism and postulates of QM. In addition, we found that, although graduate students performed significantly better than undergraduate students, their average overall score was not very high.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found that students who were enrolled in QM courses that used active learning methods, such as peer instruction and tutorials, performed better on the QMFPS than those who did not. These approaches included active learning techniques such as peer instruction [52,53], tutorials [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68], cooperative group problem solving [69], and Just-In-Time-Teaching [70,71], to help students develop a coherent knowledge structure of the formalism and postulates of QM. In addition, we found that, although graduate students performed significantly better than undergraduate students, their average overall score was not very high.…”
Section: Discussionmentioning
confidence: 99%
“…This study was focused on student learning of fundamental quantum mechanics concepts such as the wave-particle duality, single photon interference, and quantum eraser [9][10][11][12][13][14][15][16][17][18] in the context of the Mach-Zehnder Interferometer, or MZI [11,19]. The goal was to use isomorphic problems [20] with different surface features to investigate the extent to which students were able to transfer their learning in advanced quantum mechanics from the context of the MZI to the context of the double slit experiment, or DSE [21][22][23] without an explicit intervention designed to help them make the connection between the different contexts. Student difficulties with quantum mechanics as well as effective approaches to improve student learning in quantum mechanics have been investigated, e.g., see .…”
Section: Introductionmentioning
confidence: 99%
“…Nesta direção, podemos mencionar os softwares como experimentos virtuais que representam o Interferômetro Virtual de Mach-Zehnder e o Experimento da Dupla--Fenda, constantemente presentes em pesquisas que abrangem instruções didáticas direcionadas ao ensino da MQ (MÜLLER;WIESNER, 2002;SINGH, 2008;PEREI-RA;OSTERMANN;CAVALCANTI, 2009;KOHNLE et al, 2015;SINGH, 2016;MARIES;SAYER;SINGH, 2017;TREVISAN;SERRANO, 2018).…”
Section: Introductionunclassified